An action research on using the comic book Calvin and Hobbes to motivate non-major students at AIC American International School to learn vocabulary = Nghiên cứu về cách sử dụng truyện tranh Calvin and Hobbes để khuyến khích học viên không chuyên tại trườ - Lưu, Thị Thu Hà (ĐHNN, 2017)
37 p. + CD-ROM